(3ehShYI GdJQGK GdYdej GdYQHj (B/s - (3Ndjd , jGSjfs 1934-1986; (3GdYHjOj, MSf eLjOs 1955- ((3GdOhMI (B- (3bWQ (B:s (3OGQ LGeYI MeO Hf NdjaI ddfTQ ,s, 2021)
(3jHMQ GdeDda ef NdGd gPg GdehShYI (B((3ehShYI GdJQGK GdYdej GdYQHj(B) (3HCLRGFgG GdCQHYI aj KfGjG GdJQGK GdYdej GdYQHj, eMGhd JbOje UhQI Mhd gPG GdJQGK, ajcTa Yfg hYf CgejJg hYf GdEfLGRGJ hGdEHOGYGJ hGdEVGaGJ GdYdejI GdJj MbbgG CSdGafG hTcdJ JbOeG cHjQG aj GdeYQaI GdYdejI BfPGc(B. (3hjbJUQ GdeDda aj JfGhdg dgPG GdJQGK Ydi GdLGfH GdYdej efg abW, eeG gh eJUd HGdOQGSGJ GdYdejI ef WHjYI hQjGVjGJ hWH hUjOdI hgfOSI hJcfhdhLjG(B. (3hjJfGhd aj GdcJGH GdKGdK efgG GdWH hGdUjOdI YfO GdYQH, ajOQS JWhQ GdeYQaI GdWHjI hefGgL GdHMK GdWHj hYde GdJTQjM hYde GdCeQGV hYde GdLQGMI hYde GdcMGdI (B((3GdYjhf(B) (3hYde GdUjOdI (B((3GdCOhjI hGdYbGbjQ(B)s
(3GdeMJhjGJ (B: (3eLdO (B1. (3eUGOQ GdJQGK GdYdej GdYQHj hGdOQGSGJ GdEfSGfjI hGdYde GdQjGVj(B-(3eLdO (B2. (3GdYdhe GdWHjI YfO GdYQH(B-(3eLdO (B3. (3GdWH hGdUjOdI YfO GdYQH(B-(3eLdO (B4. (3OQGSGJ aj GdJQGK GdYdej GdYQHj(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B. s
Keywords: (3GdYdhe YfO GdYQHs -- (3OhGFQ eYGQas; (3GdYdhe YfO GdeSdejfs -- (3OhGFQ eYGQas; (3GdeYQaIs -- (3GdKbGaI hGdJYdes -- (3GdYQHs -- (3ehShYGJs